TEACHERSâ PERCEPTION AND PROBLEMS IN THE IMPLEMENTATION OF SCHOOL-BASED CURRICULUM (A CASE STUDY) - Kustini, Siti; ., Evidoyanti (INTEKNA, 2011)
Since 2006 (in decentralization era) Indonesia has been implementing school level curri-culum based on national standard of education (content and competence standards in particular) considering the goal of a certain level of education, learning experiences that should be provided to achieve the goal, the methods used to manage the learning expe-riences, and methods of evaluation to measure the goal achievement. The development of a school-level curriculum is a new phenomenon for the school community in Indonesia, consequently, in the early stage of its implementation some obstacles were found in a number of schools. The change in the role of schools from curriculum implementer to curriculum developer has made the school community confused. The changes of English curriculum in Indonesia are in line with the changes of the educational curriculum. This present study was intended to find out teachersâ understanding and perception on SBC as well as to identify problems faced by the teacher in the implementation of SBC parti-cularly in the English teaching. The research was conducted in SMAN 5 Cimahi, there-fore three English teachers from that school were chosen as the participants. The qualitative research design was employed in this research and the data were taken from the questionnaire with 5 (five) open question and 29 (twenty-nine) checklist question for-mat. The questionnaire was primarily used to collect the information to survey the tea-chersâ general understanding and perception as well as problems in SBC implementation. The result of the study showed that teachers possessed good understanding and percep-tion on SBC and they did not encounter any serious problems in the implementation. The successful implementation of this curriculum should be continuously maintained so that the goal of Indonesian education to develop learnersâ basic intelligence, knowledge, per-sonality, noble character, as well as skills to live independently can be achieved.